Legumes not associated and associated with millet in different soil management systems in organic bean. - Rivero Herrada, Marisol; Mozena Leandro, Wilson; De Brito Ferreira, Enderson Petrônio (REVISTA TERRA LATINOAMERICANA, 2017)
Several studies have demonstrated the benef its of using cover crops to maintain or improve soil quality and crop productivity. However, the effects of this management with organic common bean in conditions of savannah are still unknown. The objective of this study was to evaluate the effect of legumes, mucuna (Mucuna pruriens (L.) DC, pigeon pea (Cajanus cajan L.) HUTH, jack or pig bean (Canavalia ensiformis), sunn hemp (Crotalaria juncea) in monoculture and intercropped with pearl millet (Pennisetum glaucum L.) R. Br. 1810, on grain production in common bean in organic production under systems of conventional and no-tillage soil management. The experiment was conducted with the cultivar BRS Pontal, arranged in a randomized block design. Bean plants were evaluated 90 days after germination, recording the number of pods per plant, number of grains per pod (NGV), number of grains per plant (NGP), weight of 100 grains (M100G) and grain production. The results showed that the number of pods, number of grains and grain yield of common bean in the organic system were influenced by the cover crops and soil management. Mucuna associated with millet and no-tillage system was outstanding, producing the best performance in these parameters. The highest grain yield was observed with the mucuna associated with maize in the no-tillage system. The average productivity of organic grain was 3.8 Mg ha-1. The cluster analysis showed a remarkable effect of soil management systems on bean production components.